(untitled) (Web of Teachers: Inderscience Research, 2026)
The article examines the anatomical and morphological structures of the liver in 24 newborns and elderly individuals (cadavers). As a result of scientific research, it was established that the liver of newborns consists of lobules separated by connective tissue layers. Longitudinal connective tissue fibers pass under the capsule, predominantly of collagen type. Sinusoidal capillaries, hepatic cells, and central veins are clearly visible. In newborns, the weight of the liver averages 120 to 150 g, constituting approximately 4-5% of body weight. In elderly individuals, the liver surface becomes denser, and its parenchyma undergoes gradual replacement with fibrous tissue. At old age, the liver weight averages 1200-1500 g.